Klasikisme Wayang Kulit Purwa Gaya Keraton Yogyakarta - Sutriyanto Sutriyanto (Ornamen, 2010)
Wayang Kulit purwa is an original product of Indonesia culturewhich develops in accordance with the rise and fall of the kingdoms inJava Island. It has tremendous influence towards the development ofart and culture in our homeland. It was initiated by the Giyanti treatyin 1755 which split Mataram kingdom into two and it also affect thedevelopment of the wayang which goes hand-in hand with style improvementon art works. History exP.Iains that the wayang located inkeraton Yogyakarta is the legacy of several provious kings in Mataramkingdom. Sultan Hamengku Buwana I using his authority and attentiontowards arts and culture, with no exception to wayang kulit pUiwa. Succeededin bringing it to his new palace, which is in keraton KasultananYogyakarta. The development of the Yogyakarta-styled wayang inkeraton Yogyakarta always refers to the previous collection of wayangwhich is usually called kanjeng kyai, so does the wayang developed inthe keraton Surakarta. Eventually, the Yogyakarta styled wayang purwapreserves the previous style more. Which is popularly known as classicstyle, while the Surakarta styled wayang kulit purwa has shown somechanges and development from the exsiting one and it is called romanticclassic style. it is reflected from the visualization of the wayang byanalyzing the implication of the crafts shape and the use of the colorsare more striking and varying.Keyword: wayang kulit, purwa, style